2005
DOI: 10.1007/s10548-005-7901-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency MEG Activity and MRI Evaluation in Parkinson's Disease

Abstract: It is suggested that the MEG could be a complementary method in the diagnostic evaluation of PD using spatial distribution of the raw data in the frequency domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Finally, MEG studies also showed that PD is associated with a slowing of resting state oscillatory brain activity. 3,20,35 Stoffers et al 35 not only confirmed previously reported slowing, but for the first time made clear that these changes already occurred in the first clinical stages of PD in untreated patients. As an alternative to spectral analyses, some research studies have focused on the application of linear connectivity measures to explore the functional interactions between brain regions.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Finally, MEG studies also showed that PD is associated with a slowing of resting state oscillatory brain activity. 3,20,35 Stoffers et al 35 not only confirmed previously reported slowing, but for the first time made clear that these changes already occurred in the first clinical stages of PD in untreated patients. As an alternative to spectral analyses, some research studies have focused on the application of linear connectivity measures to explore the functional interactions between brain regions.…”
Section: Introductionsupporting
confidence: 54%
“…The most common alteration in PD is generalized slowing of brain activity. 3,20,29,34,35 PD patients showed a power decrease at the EEG beta band and an increase at the theta band. 34 In another study, 29 the patients presented diffuse slowing of their quantitative EEG (qEEG) when compared with age-matched controls.…”
Section: Introductionmentioning
confidence: 97%
“…In a similar sense, both EEG and MEG slowing have also been reported in other neurodegenerative diseases like mild cognitive impairment [13,36], vascular dementia [28,35,54], Lewy body dementia [18,31], major depression [34,55,56], dementia associated with Parkinson's disease [31,57,58], Pick's disease [59], Huntington's chorea [60] and progressive supranuclear palsy [31]. To extract accurate markers of AD, further studies should analyze differences in the slowing of EEG/MEG rhythms when comparing AD and the aforementioned diseases.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies using EEG or MEG have noted that there was stronger increase of power in demented as compared to non-demented PD patients (Caviness et al 2007;Neufeld et al 1994;Soikkeli et al 1991), and the latter showed the increase of power in low frequency domain (Bosboom et al 2006;Kotini et al 2005;Serizawa et al 2008;Moazami-Goudarzi et al 2008), or even in all frequency bands (Tanaka et al 2000) in comparison with controls. For example, Soikkeli et al (1991) reported an increase of h activity and a decrease of b power in demented PD patients using FFT analysis of EEG data obtained with a single occipital electrode, and Neufeld et al (1994) also suggested consistent trend of increase in the d-and h-band and a significant decrease in the a-band for demented PD patients, but both of them did not obtain similar results in non-demented patients relative to controls.…”
Section: Discussionmentioning
confidence: 98%